Case study on structured public-private sector dialogue : the experience from Botswana - Land, Anthony (ECDPM MaastrichtNL, 2002)
Provides a general synopsis of processes of public-private sector dialogue in Botswana. Traces the evolution of current structures, describes how they function and lists what are deemed to be strengths and weaknesses. Highlights the role of the main private-sector representative body and presents a list of lessons learned.